Ebullition rates and mercury concentrations in St. Lawrence river sediments and a benthic invertebrate. (21st February 2013) - Razavi, N. Roxanna; Ridal, Jeffrey J.; de Wit, William; Hickey, M. Brian C.; Campbell, Linda M.; Hodson, Peter V.
Abstract: Ebullition, the release of gas from anaerobic decomposition in sediments, was recorded in a mercury‐contaminated depositional zone (Zone 1) of the St. Lawrence River Area of Concern in Cornwall, Ontario, Canada. The aim of the present study was to test if this disturbance affected the bioavailability of total mercury (THg) and methylmercury (MeHg) in surficial sediments to a benthic invertebrate ( Echinogammarus ischnus ). Ebullition rates ranged from <1 to 2, 800 ml/m 2 daily, with methane gas comprising 29 to 84% of the total. No direct effects of ebullition were found on either abiotic (sediment or pore water THg or MeHg concentrations) or biotic (amphipod THg or MeHg concentrations) variables measured. Instead, amphipod MeHg concentrations were best predicted by pore water THg and MeHg concentrations, organic matter of surficial sediments, and water depth and location. Trend surface analyses demonstrated that a shallow, southwestern part of Zone 1 was most contaminated with pore water mercury, which decreased in a gradient toward the northeast. Further study is needed to determine if the amount of sediment resuspended by ebullition affects the spatial distribution of mercury. Environ. Toxicol. Chem. 2013;32:857–865. © 2013 SETAC